1995
DOI: 10.1007/bf00186744
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of connexin 43 in the developing tooth germ of rat

Abstract: Distribution of gap junction protein in maxillary tooth germs of 1-day-old rats was examined by immunohistochemistry, using an affinity-purified antibody specific to residues 360-376 of rat connexin (CX) 43. In 1-day-old rats, the maxillary second molar formed the shape of the cusp, but neither dentine nor enamel was formed between the cells of the dental papilla and the inner enamel epithelium. In the tooth germ, CX 43 was expressed in the cells of the stratum intermedium and the inner enamel epithelium. Labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…The temporospatial expression pattern of Amtn during tooth development needs further examination. Gja1 has been previously reported to be expressed in the cells of the stratum intermedium and the inner enamel epithelium (Pinero et al, 1994;Kagayama et al, 1995) where it is distributed exclusively at the sites of contact between odontoblasts, suggesting a function in cell to cell signaling (Fried et al, 1996). Mutations in Gja1 have been found to cause oculodentodigital dysplasia and Hallermann-Streiff syndrome, conditions that include dental anomalies (Paznekas et al, 2003;Pizzuti et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The temporospatial expression pattern of Amtn during tooth development needs further examination. Gja1 has been previously reported to be expressed in the cells of the stratum intermedium and the inner enamel epithelium (Pinero et al, 1994;Kagayama et al, 1995) where it is distributed exclusively at the sites of contact between odontoblasts, suggesting a function in cell to cell signaling (Fried et al, 1996). Mutations in Gja1 have been found to cause oculodentodigital dysplasia and Hallermann-Streiff syndrome, conditions that include dental anomalies (Paznekas et al, 2003;Pizzuti et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have found an association between CX43 and differentiation of odontoblasts (Pinero et al 1994;Kagayama et al 1995;Fried et al 14 1996;Murakami et al 2001). Murakami et al found that expression of CX43 showed an increase following odontoblast differentiation (Murakami et al 2001).…”
Section: Intercellular Communication Via Gjs Plays a Major Role In Mamentioning
confidence: 99%
“…Recently, investigations on expression and localization of CX43 in rat incisor odontoblasts and pulp cells have demonstrated that CX43 was highly expressed in young odontoblasts (Pinero et al 1994;Kagayama et al 1995;Fried et al 1996;Murakami et al 2001). Furthermore, CX43 has been shown to be a marker of viability in dental pulp tissue (Muramatsu et al 2004).…”
Section: +mentioning
confidence: 99%
“…One freeze-fracture study showed that GJs increase in size with the growth of odontoblasts and that the largest GJs can be found in young odontoblasts, which suggests a correlation between the size of GJs and cell function in dentinogenesis (Iguchi et al 1984). More recent studies have demonstrated immunohistochemically that GJs are present in dental pulp tissue and that CX43 exists between odontoblasts (Pinero et al 1994;Kagayama et al 1995;Fried et al 1996). In contrast, Su et al (1997) found no CX43 expression in rat odontoblasts.…”
Section: Discussionmentioning
confidence: 92%
“…The presence of GJs between odontoblasts and nerve fibers has been suggested but has not been conclusively established (Gunji 1982;Koling and RaskAndersen 1984;Fried et al 1996). CX43 expression in odontoblasts has been demonstrated clearly in the developing molar tooth germ of rats (Pinero et al 1994;Kagayama et al 1995;Fried et al 1996), but the expression and localization of CX43 in rat incisal odontoblasts has not yet been examined.…”
Section: Introductionmentioning
confidence: 95%